Distribution and abundance of Syacium ovale larvae (Pleuronectiformes: Paralichthyidae) in the Gulf of California - Aceves-Medina, Gerardo (Universidad de Costa Rica, 2003)
The spawning season of the tonguefish Syacium ovale (Günter 1864) was determined by an analysis of the distribution of preflexion stage larvae in the Gulf of California. The larvae were collected during eight oceanographic surveys between 1984 and 1987. The spawning of this species starts in early summer and ends at the beginning of fall, with the highest reproductive activity in mid summer. The central and southern regions of the Gulf are the most important reproductive area. Spawning is associated with high sea surface temperatures and low plankton biomass, both of which are characteristics of the tropical current that invades the study area during summer.